Biomass productivity-based mapping of global land degradation hotspots - Quang Bao Le; Ephraim Nkonya; Alisher Mirzabaev (University of Bonn, Center for Development Research (ZEF), 2014)
Land degradation is a global problem affecting negatively the livelihoods and food security of billions of people, especially farmers and pastoralists in the developing countries. Eradicating extreme poverty without adequately addressing land degradation is highly unlikely. Given the importance and magnitude of the problem, there have been recurring efforts by the international community to identify the extent and severity of land degradation in global scale. As discussed in this paper, many previous studies were challenged by lack of appropriate data or shortcomings of their methodological approaches. In this paper, using global level remotely sensed vegetation index data, we identify the hotspots of land degradation in the world across major land cover types. In doing so, we use the long-term trend of inter-annual vegetation index as an indicator of biomass production decline or improvement. Besides the elimination of technical factors, confounding the relationship between the indicator and the biomass production of the land, we apply a methodology which accounts for masking effects of both inter-annual rainfall variation and atmospheric fertilization. We also delineate the areas where chemical fertilization could be hiding the inherent land degradation processes. Our findings show that land degradation hotpots cover about 29% of global land area and are happening in all agro-ecologies and land cover types. Land degradation is especially massive in grasslands. About 3.2 billion people reside in these degrading areas. However, the number of people affected by land degradation is likely to be higher as more people depend on the continuous flow of ecosystem goods and services from these affected areas. As we note in the paper, this figure, although, does not include all possible areas with degraded lands, it identifies those areas where land degradation is most acute and requires priority actions in both in-depth research and management measures to combat land degradation. Our findings indicate that, in fact, land improvement has also occurred in about 2.7% of global land area during the last three decades, providing a support that with appropriate actions land degradation trend could be reversed, and that the efforts to address land degradation need to be substantially increased, at least by a factor, to attain the vision of Zero Net Land Degradation. We also identify concrete aspects in which these results should be interpreted with caution, the limitations of this work and the key areas for future research.
Keywords: Q01; Q15; Q23; Q24; Q56; 330; land degradation hotspots; mapping; carbon fertilization; economics of land degradation